Estimating the attributable burden of preterm birth and low birth weight due to maternal ozone exposure in nine Chinese cities. (1st February 2020) - Yang, Yin; Liang, Zhijiang; Ruan, Zengliang; Zhang, Shiyu; Zhao, Qingguo; Lin, Hualiang
Abstract: Background: Maternal exposure to various air pollutants is one crucial contributor to adverse birth outcomes, however, the effects of ozone (O3 ) exposure have remained largely unknown, especially attributable burden in different exposure windows. Methods: We performed a birth cohort study in nine Chinese cities in Guangdong Province during 2014–2017. The mothers were included in this study at their first time hospital visits for pregnancy in the nine cities, and followed up till the delivery. Air pollution exposure of each participant was estimated using the daily data from air monitoring stations in the mother's residential district. The status of low birth weight (LBW) and preterm birth (PTB) was ascertained based on standard criteria and collected from the electronic medical record. We applied a Cox regression model to estimate the associations and the attributable burden. Results: Among the 1, 455, 026 mother-and-live-birth pairs, 64, 028 (4.40%) were PTB, and 57, 618 (3.96%) were LBW. After adjustment for potential confounders, the hazard ratios for each 10 μg/m 3 increase in O3 concentrations during trimester 1, trimester 2, one week prior and four weeks prior were 1.025 (95% CI: 1.020, 1.030), 1.033 (95% CI: 1.028, 1.039), 1.013 (95% CI: 1.010, 1.017) and 1.016 (95% CI: 1.011, 1.020) for PTB, 1.035 (95% CI: 1.030, 1.040), 1.035 (95% CI: 1.029, 1.041), 1.013 (95% CI: 1.009, 1.017) and 1.016 (95% CI: 1.012, 1.021) for LBW, respectively. The estimated attributable fractions at one week prior to delivery were 0.86% (95% CI: 0.39%, 9.26%) of PTB and 0.87% (95% CI: 0.60%, 1.14%) of LBW. Conclusions: This study indicates that maternal exposure to O3 might lead to increased risk of PTB and LBW, and is responsible for non-negligible burden of PTB and LBW in the study region. Highlights: Maternal O3 exposure might lead to increased risk of PTB. Maternal O3 exposure might lead to increased risk of LBW. These associations were not confounded by PM2.5, NO2, and SO2 concentrations.